PENGGUNAAN PEMBATAS ALIRAN (KATUP) JENIS SWING CHECK PADA KERAN AIR UNTUK EFISIENSI AIR WUDU - Aulia Rohendi; Teuku Muhammad Ashari; Muhammad Daudsyah (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2022)
In Islam, the most frequent need for water is when performing ablution activities. Prophet Muhammad SAW used only 1 mudd of water (about two-thirds of a liter) or about 0.67 liters for ablution. This study aims to determine the efficiency of using a Swing Check type of flow limiter on a water faucet related to ablution activities. The results showed that the flow limiter (valve) of the Swing Check type was able to efficiently use water in an average of 43%. With the Swing Check valve wudu volume per individual is 17.68 l/person before the flow limiter is used this valve and 10.09 liters/person. With this research, it is hoped that in the future we can update technology that can save water, not only in saving water but also in maintaining the existence of water, especially the involvement of water conservation also plays an important role in water conservation.